The possibilities of antioxidant neuroretinoprotection in the treatment of primary open-angle glaucoma - Egorov, E A; Kuroyedov, A V; Gavrilova, N A; Yavorskiy, A E; Gornostaeva, E A (Vestnik oftal'mologii, 2025)
This study evaluated the effect of sequential therapy with different dosages of Mexidol on the stabilization of glaucomatous optic neuropathy (GON) in patients with primary open-angle glaucoma (POAG). The study included 80 patients (160 eyes) with stage II and III POAG, randomized into three groups comparable by age, gender, and distribution of glaucoma stage. All patients received sequential therapy with Mexidol (14 days parenterally followed by 90 days orally). Groups were defined as follows: group 1 - "high dosage", group 2 - "low dosage", and group 3 - "placebo". Before therapy initiation and at completion, static automated perimetry was used to determine the mean deviation (MD) and pattern standard deviation (PSD) of retinal light sensitivity, as well as the number of first- and second-order scotomas. Subgroup analysis was performed based on treatment response. Glaucoma progression during therapy was analyzed using the Kaplan-Meier method. A statistically significant improvement in MD compared with baseline was observed after the course of therapy in both the high- and low-dose groups for moderate ( <0.001) and advanced ( <0.05) stages of POAG. There was a trend toward PSD improvement in the groups of both dosages, but absent in the placebo group. Unlike the treatment groups, the placebo group showed a negative trend toward an increase in relative first- and second-order scotomas. Subgroup comparison revealed significant differences among the "high dosage", "low dosage", and "placebo" groups ( =0.002, Pearson's χ² test). Kaplan-Meier analysis demonstrated a high probability of glaucoma progression in the "placebo" group and a significantly lower probability ( <0.01) in both "high dosage" and "low dosage" Mexidol groups. Mexidol therapy improves retinal light sensitivity, stabilizes the number of relative first- and second-order scotomas, and reduces the likelihood of GON progression. The dose-dependent effect of Mexidol was demonstrated.